A study of the suitability of some farm wastes as substrate for mushroom spawn production - Basilio, Porferio Latina 1938- ([Quezon City s.n.], 1974)
The aim of this study was to determine how different materials considered as farm wastes compare in terms of suitability to substrate in mushroom spawn production and how varying amounts of moisture in the substrate affect the mycelial growth of the mushroom organism during incubation period. This paper also designed an experiment which may serve as a laboratory activity for high school and college students of science.
Thesis (M.A.T.)--University of the Philippines.
Keywords: Mushroom culture